THE IMPACT OF MARKETING ON THE IMAGE AND REVENUE OF INSURANCE COMPANIES - Rashidova Dildora Rasul qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This scientific article provides a comprehensive analysis of the impact of marketing activities in insurance companies on the formation of corporate image and financial performance indicators. The study focuses on examining the theoretical foundations of insurance marketing and its practical application mechanisms. Based on a review of scientific literature, the influence of insurance company image on customer trust and market competitiveness is highlighted. The role of marketing strategies in increasing demand for insurance products is substantiated. Drawing on the scientific works of foreign and domestic researchers, the specific features of insurance marketing are analyzed. The study examines the current state of development and institutional foundations of the insurance market in Uzbekistan. The impact of state-adopted regulatory and legal documents on insurance marketing is evaluated. The importance of marketing communications and branding policy is revealed. The research results indicate a positive relationship between marketing activities and the revenues of insurance companies. The conclusions obtained are of significant importance for the strategic management of insurance company activities.